Fabrication and characterization of oil-in-water pickering emulsions stabilized by ZEIN-HTCC nanoparticles as a composite layer. (October 2021) - Cao, Mengna; Liu, Chengzhi; Shi, Jieyu; Ni, Fangfang; Qi, Jiaming; Shen, Qing; Huang, Min; Ren, Gerui; Tian, Shiyi; Lin, Quanquan; Lu, Xiaoxin; Lei, Qunfang; et al.
Graphical abstract: Highlights: ZEIN-HTCC nanoparticles were fabricated as Pickering stabilizers. The addition of HTCC can improve the physicochemical stability of emulsion. Pickering emulsions showed good stability against salt ion, pH and storage time. ZEIN-HTCC nanoparticles formed a composite layer around the surfaces of oil droplets. Abstract: In this work, the ZEIN-HTCC nanoparticles formed by zein and N-(2-hydroxy)propyl-3-trimethylammonium chitosan chloride (HTCC) were used as stabilizers to prepare oil-in-water (O/W) Pickering emulsions. The preparation conditions including shearing time, volume fraction of corn oil, mass ratio of ZEIN:HTCC and total concentration of ZEIN-HTCC of emulsions were optimized by measuring the droplet size, zeta potential, PDI and surface tension of emulsions. The ZEIN-HTCC emulsions are stable at the pH range of 4–9 and in the low salt ion concentrations up to 0.2 mol L −1, and can keep stable up to 21 d during low temperature storage. Fourier transform infrared spectroscopy (FTIR), the confocal laser scanning microscope (CLSM) and scanning electron microscopy (SEM) were used to analyze the interaction between emulsion components, revealing that zein and HTCC form a composite layer by flocculation to adsorb on the surface of oil droplets, thus preventing emulsion droplets from aggregation. This novel, long-term stable, surfactant-free, and edible zein-based Pickering emulsion could be used as potential carriers for lipophilic nutrients delivery.